Descriptive Analysis of Psychological and Demographic Resources Among Entrepreneurs Graduated from State Universities in Padang - Agriqisthi .; Nadratun Nafisah Abdul Wahab; Rafiduraida Abdul Rahman (Jurnal Ekonomi Manajemen dan Bisnis (JEMB), 2025)
This study provides a detailed descriptive analysis of the demographic profile and self-reported psychological resources essential for entrepreneurship among a cohort of nascent university graduates in Padang, West Sumatra, Indonesia. Facing increasing structural unemployment challenges, a sample of 150 fresh graduate entrepreneurs from state universities in Padang was examined. The analysis focused on descriptive statistics for key constructs: Entrepreneurial Resilience (R), Internal Locus of Control (ILOC), Achievement Motivation (AM), Materialism Motivation (MM), and Entrepreneurial Self-Efficacy (ESE). The findings reveal a highly persistent, dual-motivated (intrinsic mastery and extrinsic financial) cohort, with Materialism Motivation and Achievement Motivation items registering the highest mean scores. Conversely, while still high, self-efficacy in specific outcomes (ESE) demonstrated the lowest comparative mean. This descriptive insight highlights the strong, pragmatic drive—necessitated by the competitive urban environment—that underpins the pursuit of entrepreneurship in this emerging market. This paper establishes a crucial psychological profile for this demographic, offering foundational data for future intervention design and policy formulation.